No evidence of effects or interaction between the widely used herbicide, glyphosate, and a common parasite in bumble bees - Straw, Edward A.; Brown, Mark J.F. (PeerJ, 2021)
Background Glyphosate is the world’s most used pesticide and it is used without the mitigation measures that could reduce the exposure of pollinators to it. However, studies are starting to suggest negative impacts of this pesticide on bees, an essential group of pollinators. Accordingly, whether glyphosate, alone or alongside other stressors, is detrimental to bee health is a vital question. Bees are suffering declines across the globe, and pesticides, including glyphosate, have been suggested as being factors in these declines. Methods Here we test, across a range of experimental paradigms, whether glyphosate impacts a wild bumble bee species, Bombus terrestris. In addition, we build upon existing work with honey bees testing glyphosate-parasite interactions by conducting fully crossed experiments with glyphosate and a common bumble bee trypanosome gut parasite, Crithidia bombi. We utilised regulatory acute toxicity testing protocols, modified to allow for exposure to multiple stressors. These protocols are expanded upon to test for effects on long term survival (20 days). Microcolony testing, using unmated workers, was employed to measure the impacts of either stressor on a proxy of reproductive success. This microcolony testing was conducted with both acute and chronic exposure to cover a range of exposure scenarios. Results We found no effects of acute or chronic exposure to glyphosate, over a range of timespans post-exposure, on mortality or a range of sublethal metrics. We also found no interaction between glyphosate and Crithidia bombi in any metric, although there was conflicting evidence of increased parasite intensity after an acute exposure to glyphosate. In contrast to published literature, we found no direct impacts of this parasite on bee health. Our testing focussed on mortality and worker reproduction, so impacts of either or both of these stressors on other sublethal metrics could still exist. Conclusions Our results expand the current knowledge on glyphosate by testing a previously untested species, Bombus terrestris, using acute exposure, and by incorporating a parasite never before tested alongside glyphosate. In conclusion our results find that glyphosate, as an active ingredient, is unlikely to be harmful to bumble bees either alone, or alongside Crithidia bombi.
Keywords: Bees; Pesticides; Glyphosate; Herbicides; Crithidia; Multiple stressors; Weedkillers; Parasites; Crithidia bombi; Trypanosome